Navigating remote work:the role of corporate social responsibility in boosting employee engagement. - Núñez-Sánchez, José Manuel; Molina-Gómez, Jesús; Mercade-Mele, Pere; Fernández Miguélez, Sergio Manuel (Emerald, 2024)
Purpose – This paper investigates the relationship between teleworkers’ perceptions of corporate social responsibility (CSR) and employee engagement (EE) in remote work. Design/methodology/approach – A quantitative research approach was used, involving a questionnaire distributed via convenience sampling. Data from 205 valid responses from teleworking employees in Spain were analysed using structural equation modelling to test the hypothesis regarding the association between CSR and EE. Findings – The study found that CSR’s social and environmental dimensions positively impact EE among teleworkers. However, the economic dimension of CSR only partially influences EE in a telework setting. Practical implications – The findings suggest organisations can enhance EE during telework periods by focusing on social and environmental CSR initiatives. This approach can mitigate the reduced EE associated with remote work, improving organisational performance, productivity, satisfaction and employee well-being. Originality/value – This study provides empirical evidence on the positive effects of CSR’s social and environmental dimensions on EE in a telework context, offering valuable insights for organisations navigating the post-pandemic landscape. Also, specific CSR strategies can establish a competitive advantage by fostering a motivated and engaged remote workforce.
Navegando por el trabajo a distancia: El papel de la responsabilidad social corporativa en el fomento del compromiso de los empleados
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/23862
Keywords: Responsabilidad social de la empresa; Employee engagement; Corporate Social Responsibility; Telework; Human Resource Management; Structural model